Phospholipase D in Cell Signaling: From a Myriad of Cell Functions to Cancer Growth and Metastasis - Gomez-Cambronero, Julian (American Society for Biochemistry and Molecular Biology, 2014)
Phospholipase D (PLD) enzymes play a double vital role in cells: they maintain the integrity of cellular membranes and they participate in cell signaling including intracellular protein trafficking, cytoskeletal dynamics, cell migration, and cell proliferation. The particular involvement of PLD in cell migration is accomplished: (a) through the actions of its enzymatic product of reaction, phosphatidic acid, and its unique shape-binding role on membrane geometry; (b) through a particular guanine nucleotide exchange factor (GEF) activity (the first of its class assigned to a phospholipase) in the case of the mammalian isoform PLD2; and (c) through protein-protein interactions with a wide network of molecules: Wiskott–Aldrich syndrome protein (WASp), Grb2, ribosomal S6 kinase (S6K), and Rac2. Further, PLD interacts with a variety of kinases (PKC, FES, EGF receptor (EGFR), and JAK3) that are activated by it, or PLD becomes the target substrate. Out of these myriads of functions, PLD is becoming recognized as a major player in cell migration, cell invasion, and cancer metastasis. This is the story of the evolution of PLD from being involved in a large number of seemingly unrelated cellular functions to its most recent role in cancer signaling, a subfield that is expected to grow exponentially.